E-Comic of Folklore in the Javanese Language to Increase 4th Graders' Learning Outcomes - Setiawan, Deni; Yuniarti, Yustina Dwi; Rahmadani, Ni Kadek Aris (Universitas Islam Negeri Raden Intan Lampung, 2022)
Based on the initial identification of research on the Javanese lessons, learning media is less attractive and innovative. To maximize students' activities and learning outcomes, the researchers developed the Javanese e-comic media. The researchers employed the simplified Borg and Gall model for research and development. Following the conditions of the research, the research steps include 1) identifying potential problems; 2) collecting data; 3) designing media; 4) validating the media; 5) revising; and (6) mass-producing. Data collection with non-test techniques, interviews, teacher and student needs, and documentation methods. The results showed that E-comics Javanese folklore material was declared very feasible, which is the result of this study. The material expert assessment obtained 91.42 percent in the very feasible category. Furthermore, the media experts’ assessment obtained 87 percent in the feasible category. Positive students and teachers’ responses to the media were 89 percent and 98.20 percent in the feasible category. Finally, E-comics with folklore material are feasible to be used in Javanese lessons. Through the Javanese folklore E-Comic developed, it has implications for students to be more receptive to learning and attract students' attention to learning.